Numerical modelling of the effects of porosity changes on the mechanical properties of nuclear graphite - Berre, C; Fok, S; Marsden, B; Babout, L; Hodgkins, A; Marrow, T; Mummery, P (2006)
Finite Element (FE) models based on three-dimensional images from X-ray tomography are used to study the relationships between the microstructure and the bulk mechanical properties of nuclear graphite. The increase in porosity due to oxidation is simulated by setting different thresholds to the grey-scale of the images. The numerical predictions seem to follow the Knudsen law and show good agreement with experiments. © 2006 Elsevier B.V. All rights reserved.